The Value of Character Education in Surah Al-An'am Verses 151-153 A Comparison Study of Tafsir Al-Misbah and Interpretation of Al-Azhar - Rohmatul Azizah; Khubni Maghfirotun (Rihlah Review: Jurnal Pendidikan Islam, 2023)
In this article, the researcher wants to elaborate more on the Character Values ​​ at Surah Al-An'am Verses 151-153 in the Tafsir Al-Misbah and the Tafsir Al-Azhar and conduct a comparative study to find out the similarities and differences in values. Therefore, this research is expected to explore the character values ​​in it so that it can be applied in daily life. Character education is something that involves actions that educate and benefit both oneself and others and have a positive impact, with good character, it is hoped that someone will apply religious teachings in accordance with what should be applied. This type of research is library research that uses a historical approach. The data collection uses the documentation method and data analysis is carried out using content analysis techniques.